African cosmopolitanism and the Atlantic: trade, imperial contact and relating to the past in the Niger Delta (nineteenth to twenty-first centuries) - Binter, JTS (2020)
This thesis analyses the role of material culture in shaping imperial contact in the Niger Delta, a centuries-long hub for transatlantic trade, and examines the ways in which people use the remnants of this material culture to relate to the past in Nigeria’s petro-state today. Based on sixteen months of fieldwork in Nigeria and London, it gives a nuanced account of the politicisation of transatlantic encounters in the current political economy of oil. Drawing on Mikhael Bakhtin’s (1981) notion of ‘chronotope’ and Kristina Wirtz’s (2014) concept of ‘temporality-emplacement’, it moves beyond the often-contested concepts of ‘history’ and ‘memory’ and looks at the performative modes with which people use material culture to relate to the past, stake claims in the present and envision possible futures. The concept of chronotopes allows for a better understanding of how people perform time and space with help of ‘things’, including images, artefacts, bodies and the environment, and thus create worlds which allow particular subjectivities to emerge. In the Niger Delta, where African merchant elites have been ‘seeing and acting beyond local environments’ (Prestholdt 2008) for centuries, these subjectivities are predominantly cosmopolitan. Gifts from transatlantic trade and international commodities fostered cosmopolitan lifestyles and identities. Today, it is this cosmopolitan reach that makes the remnants of transatlantic encounters particularly valuable for the formation of heritage and the contestation of land and, thus, mineral rights. Taking a crisis of leadership in the Kingdom of Warri and a film made by expatriate Nigerians in London as starting points, the thesis compares the competing chronotopes of Pentecostalism, sacred kingship, ancestral worship, theatre and museums in Nigeria’s postcolony and highlights their entanglements with intra- and interethnic as well as national-regional and transnational politics. It gives insights into the interdependencies of cultural practices and shifting political economies and contributes to a better understanding of Africa’s relationship with the Atlantic world.